Pengaruh alat penyajian disposable terhadap sisa makanan pasien di ruang rawat inap RSUP Dr. Kariadi Semarang - Tiurma Heryawanti P; Endy Paryanto Prawirohartono; Toto Sudargo (Jurnal Gizi Klinik Indonesia, 2004)
Background: Food service success relates to patient plate waste. Patient plate waste in Indonesia Hospitals could be more than 25%. Cause of patient plate waste in Hospital is lack of food and equipment quality. Almost of 32.8% patients in 10 hospitals model in Indonesia clarify that appearance, cleanliness, and equipment are good.Objective: The aim of theses research was to identify the effect of serving utensils and the other factors to the plate waste.Methods: This was a Quasi Experiment study using pre posttest with control. Study subject consisted of 45 patients in the treatment group and 45 patients in the control group. Data were analyzed descriptively and whereas t-test, Fisher Exact test, Chi-Square were performed to differentiate the proportions and means in two groups. The effect of several variables on plate waste was calculated using logistic regression on analysis.Results: This study showed that no significant difference of taste, appearance, attitude of the staff who serve meals, service timeliness, kind of food, kind of diseases and environment to patient plate waste (p>0.05). There was no significant effected of the serving disposable utensils on patient plate waste (p>0.05).Conclusion: The type of serving disposable utensils was no a significant factor effected the plate waste.